Strain and serenity: exploring the interplay of stress, burnout, and well-being among healthcare professionals - Dobešová Cakirpaloglu, Simona; Cakirpaloglu, Panajotis; Skopal, Ondřej; Kvapilová, Barbora; Schovánková, Tereza; Vévodová, Šárka; Greaves, Jane Peta; Steven, Alison (Frontiers in Psychology, 2024)
Introduction Stress and burnout can negatively affect performance, mental health, and the overall well-being of healthcare workers. The study aims to examine the prevalence of stress and burnout, and investigate links between stress, burnout, mental state, and well-being among healthcare workers in the Czech Republic. Methods A cross-sectional survey was conducted in the Czech Republic, focusing on healthcare professionals working in various healthcare settings. A total of 1,064 healthcare workers participated in the study. A standardized questionnaire battery was used, consisting of the Maslach Burnout Inventory (MBI), Perceived Stress Scale (PSS) and Supso-7 measuring mental state. Separate correlation and multiple regression analyses were conducted. Results 46.24% of the healthcare workers reported high levels of emotional exhaustion, 25.56% reported high levels of depersonalization, 24.15% reported low levels of personal accomplishment, while 11.18% reported high levels of perceived stress. The findings revealed that emotional exhaustion, a core component of burnout, was associated with increased feelings of anxiety and depression. Perceived stress was also linked to anxiety and depression, while personal accomplishment appeared to mitigate depression and support positive psychological well-being. Conclusion The study provides promising evidence suggesting that addressing stress and emotional exhaustion, while fostering a sense of personal achievement, could lead to improvements in the mental health and work performance of healthcare workers. These findings highlight the importance of addressing burnout and stress management strategies to support the overall well-being of healthcare professionals.